Misinformation, internet honey trading and beekeepers drive a plant invasion - Magdalena Lenda; Piotr Skórka; Karolina Kuszewska; Dawid Moroń; Michał Bełcik; Renata Baczek Kwinta; Franciszek Janowiak; David H. Duncan; Peter A. Vesk; Hugh P. Possingham; Johannes M. H. Knops (Ecology Letters, 2021)
Biological invasions are a major human induced global change that is threatening global biodiversity by homogenizing the world’s fauna and flora. Species spread because humans have moved species across geographical boundaries and have changed ecological factors that structure ecosystems, such as nitrogen deposition, disturbance, etc. Many biological invasions are caused accidentally, as a byproduct of human travel and commerce driven product shipping. However, humans also have spread many species intentionally because of perceived benefits. Of interest is the role of the recent exponential growth in information exchange via internet social media in driving biological invasions. To date, this has not been examined. Here, we show that for one such invasive species, goldenrod, social networks spread misleading and incomplete information that is enhancing the spread of goldenrod invasions into new environments. We show that the notion of goldenrod honey as a “superfood” with unsupported healing properties is driving a demand that leads beekeepers to produce goldenrod honey. Social networks provide a forum for such information exchange and this is leading to further spread of goldenrod in many countries where goldenrod is not native, such as Poland. However, this informal social information exchange ignores laws that focus on preventing the further spread of invasive species and the strong negative effects that goldenrod has on native ecosystems, including floral resources that negatively impact honeybee performance. Thus, scientifically unsupported information on “superfoods” such as goldenrod honey that is disseminated through social internet networks has real world consequences such as increased goldenrod invasions into novel geographical regions which decreases native biodiversity.